Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1212/wnl.0000000000007536
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in neuroZika

Abstract: ObjectiveTo characterize the full spectrum, relative frequency, and prognosis of the neurologic manifestations in Zika virus (ZIKV) postnatal infection.MethodsWe conducted an observational study in consecutive ZIKV-infected patients presenting with neurologic manifestations during the French West Indies 2016 outbreak.ResultsEighty-seven patients, including 6 children, were enrolled. Ninety-five percent of all cases required hospitalization. Guillain-Barré syndrome was the most frequent manifestation (46.0%) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Clinical evidences have shown that ZIKV may result in encephalitis and other myelitis, attesting our results (Muñoz et al, 2016;Da Silva et al, 2017;Pereira et al, 2017;Tolosa et al, 2017;Capasso et al, 2019). As previously observed by Lannuzel et al (2019), long-term sequelae were frequenting in children and adult patients from ZIKV-outbreak in Guadeloupe and Martinique islands. They identified not only Guillain-Barré syndrome (GBS), but other disorders involving both, central and peripheral nervous system, as encephalitis or encephalomyelitis, in addition to nerve palsies.…”
Section: Molecular Markers Of Potential Clinical Outcomessupporting
confidence: 91%
“…Clinical evidences have shown that ZIKV may result in encephalitis and other myelitis, attesting our results (Muñoz et al, 2016;Da Silva et al, 2017;Pereira et al, 2017;Tolosa et al, 2017;Capasso et al, 2019). As previously observed by Lannuzel et al (2019), long-term sequelae were frequenting in children and adult patients from ZIKV-outbreak in Guadeloupe and Martinique islands. They identified not only Guillain-Barré syndrome (GBS), but other disorders involving both, central and peripheral nervous system, as encephalitis or encephalomyelitis, in addition to nerve palsies.…”
Section: Molecular Markers Of Potential Clinical Outcomessupporting
confidence: 91%
“…However, the disease has been linked to several neurologic manifestations in children and adults such as Guillain-Barré syndrome and peripheral nerve involvement, and ophthalmic complications such as retinal and optic nerve abnormalities. Vertical transmission has been associated with spontaneous abortion and stillbirth, and also with congenital malformations in newborns including but not limited to microcephaly [5,15,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental models and human studies have shown that ZIKV has an exquisite affinity for human neural progenitor cells that might explain pre-natal neural damage (8), the mechanisms that induce neuronal damage and explains other neurological manifestations in adults are not clearly understood. Further, severe manifestations in adults and infants have received considerable attention given its conspicuousness and ramifications but it is reasonable to hypothesize that ZIKV infection may cause subclinical or mild disease, which might include neurocognitive impairment during acute infection or over the long term (9)(10)(11). In this study, we aimed to explore whether ZIKV infection may cause subclinical or mild neurocognitive alterations, estimate its frequency and duration, and to compare it to other acute illnesses in a cohort of people with suspected Zika infection in Mexico.…”
Section: Introductionmentioning
confidence: 99%